2018
DOI: 10.1002/bjs.10682
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of outcomes following resection of the primary tumour in patients presenting with metastatic colorectal cancer

Abstract: Primary tumour resection may provide a modest survival advantage in patients presenting with metastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…The NCCN guidelines recommend surgery only in symptomatic patients, but non‐curative resection in asymptomatic patients has been advocated by different authors to prevent emergency procedures and some studies suggest a survival benefit when surgery is performed. On the other hand, colorectal surgery, in general, is associated with high morbidity rates which are even higher in patients with metastatic colorectal cancer . Postoperative complications may result in delayed adjuvant therapy or even precluding postoperative chemotherapy or radiation altogether, as noted by Hendren et al It is to be expected that with the improvements in chemotherapeutic agents, the number of surgical interventions should decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCCN guidelines recommend surgery only in symptomatic patients, but non‐curative resection in asymptomatic patients has been advocated by different authors to prevent emergency procedures and some studies suggest a survival benefit when surgery is performed. On the other hand, colorectal surgery, in general, is associated with high morbidity rates which are even higher in patients with metastatic colorectal cancer . Postoperative complications may result in delayed adjuvant therapy or even precluding postoperative chemotherapy or radiation altogether, as noted by Hendren et al It is to be expected that with the improvements in chemotherapeutic agents, the number of surgical interventions should decline.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, colon cancer patients were older with a significant difference in the resectable cohort (mean 59. 19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) .269 19 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 17 (14)(15)(16)(17)(18)(19)(20)(21) .082…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In addition, a decrease in tumor burden after PTR is expected to increase the potential survival. Several retrospective studies and meta-analyses have reported survival benefits of PTR compared with upfront chemotherapy [ 3 , 4 , 5 ]. According to the analysis of the Surveillance, Epidemiology, and End Results (SEER) database by Tarantino et al [ 6 , 7 ], PTR results in prolonged overall and cancer-specific survival compared to upfront chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Human colorectal cancer (CRC) is the second leading cause of cancer death in the US, and~25% of patients with CRC are incurable at the time of diagnosis [1,2]. Genetic heterogeneity is inherent to this disease, providing tumor cells with the ability to rapidly adapt and resist treatments [3,4].…”
Section: Introductionmentioning
confidence: 99%